Dynamic Entry and Exit Linkages in the Brazilian Manufacturing Industry: An Econometric Investigation - Marcelo Resende; Eduardo P. Ribeiro; Rodrigo M. Zeidan (Center for Economic Studies and ifo Institute (CESifo), 2013)
The paper investigates dynamic linkages between entry and exit rates in Brazilian manufacturing in the context of 231 (4-digits) industries during the 1996-2005 period. The empirical analysis focuses on the estimation of a dynamic panel data for entry and exit rates and controls for the business cycle. The empirical evidence is consistent with a multiplier effect where synergetic factors prevail either by entry inducing entry or by exit inducing exit. Evidence partially supports a competition effect that could be related to a selection process favouring efficiency, as exit induces entry. The business cycle control variable appears to play no role. The results are similar, though not identical to previous evidence for developed countries.
Keywords: L10; C33; 330; entry and exit rates; dynamic panel data